Pembayaran Uang Pengganti Terhadap Tindak Pidana Korupsi - D. Novrian Syahputra (KEADILAN PROGRESIF, 2015)
The development of the problem corruption in Indonesia is now so severe and become a problem that is extraordinary because it has increased and spread to the whole society. Recognizing the complexity of the problem of corruption in the midst of crisis multimedimensial as well as a real threat that is bound to happen that the impact of this  crime .Then corruption can be categorized as a national problem that must be dealt with seriously by the balance of measures firmly and clearly to involve all the potential that exists in the society, especially the government and law enforcement officials .